Economic Drivers of Climate Migrant Settlement: Insights from ASEAN - Ta, Khanh-Linh; Ly, Thu-Ha (Journal of Contemporary Sociological Issues, 2025)
Migration patterns among ASEAN Member States (AMS) are diverse and complex, with nations like Brunei Darussalam, Malaysia, Singapore, and Thailand serving as net immigration countries. Conversely, Indonesia, the Philippines, and Vietnam are among the world’s largest emigration nations. Most migration within AMS is temporary and primarily consists of low-skilled workers, while many skilled workers from the region seek permanent migration opportunities in OECD countries. Economic factors serve as the primary drivers of migration; however, these are often intertwined with environmental, social, and economic influences. By examining the intersection of economic motivations and environmental pressures, this research focuses on economically driven migration (labor migration) in the context of economically driven climate migration. The study aims to understand climate-induced migration in ASEAN and investigates the role of OECD countries, which have become key destinations for ASEAN migrants. The research explores how migration patterns are affected by climate change's economic and environmental challenges and how these pressures shape migration flows within and beyond the region. Lastly, the research analyzes how ASEAN countries have recognized and responded to the economic challenges related to climate-induced migration, particularly amid rapid regional growth. Moreover, this article argues that the current migration frameworks in these countries of origin might require improvement, mainly to protect climate migrants better and enhance the understanding of ASEAN’s stance on this issue. Ultimately, this research promotes strategies for managing climate-induced migration within ASEAN and in collaboration with OECD countries, contributing to a global dialogue on climate migration.       Keywords: climate migration, labour migration, Southeast Asia, ASEAN, OECD